Assessment of Changes in Functional Brain Connectivity During Depression Treatment with TMS Using Granger Causality Based Methods - Mikalkeniene, Gajane; Dapsys, Kastytis (Vilnius University Open Series, 2023)
Directed transfer function (DTF) method was used to assess brain connectivity disturbances in depression. The results were depicted as a brain model with the electroencephalographic (EEG) registration points, through which the directions of bioelectric activity transfer are defined. Transcranial magnetic stimulation (TMS) is used as an alternative treatment for drug-resistant depression and is considered to restore impaired connections. The combination of TMS and EEG allows to study changes of functional brain connectivity (FBC) in a non-invasive way. It was found that the FBC of resistant patients differed more from that of healthy subjects than in non-resistant patients. The largest changes in connectivity were identified in theta frequency.
Keywords: functional brain connectivity; electroencephalography; depression; direct transfer function; transcranial magnetic stimulation